THE EFFECT OF SENSATIONAL ADVERTISING, CELEBRITY ENDORSE, AFFILIATE MARKETING AND PRODUCT VARIATION ON CONSUMER BUYING INTEREST IN SCARLETT PRODUCTS (Case Study of Economics and Business Students of Universitas Malikussaleh) - Ulan Tari; M. Subhan; Heriyana; T. Edyansyah (RADJA PUBLIKA, 2025)
This research aims to determine the influence of Sensational advertising, Celebrity Endorsement, Affiliate Marketing, and product variations on interest in purchasing Scarlett Skincare products among students at the Faculty of Economics and Business, Universitas Malikussaleh. The research method used in this research is a quantitative method. The instruments in this research use validity tests, reliability tests, classic assumption tests used, namely normality tests, multicollinearity tests and heteroscedasticity tests, determination tests (R2) and hypothesis tests (t). This research was conducted on economics and business students at Universitas Malikussaleh. In this research, the data used was primary data obtained by distributing questionnaires to 100 respondents. The data analysis technique used is multiple linear regression analysis with the help of the SPSS 26.0 program. The results of this research show that partially, each variable, namely, Sensational advertising has a significant effect on buying interest, Celebrity endorsement has a significant effect on buying interest, Affiliate Marketing has a positive and significant effect on buying interest and product variety has a positive and significant effect on buying interest.